Overexpression of thioredoxin‐2 attenuates age‐related muscle loss by suppressing mitochondrial oxidative stress and apoptosis - Huibin Tang; Michael Kim; Myung Lee; Kellie Baumann; Francesca Olguin; Hao He; Yoyo Wang; Bowen Jiang; Shuhuan Fang; Jinguo Zhu; Kun Wang; Hui Xia; et al. (Wiley, 2022)
Abstract Background Skeletal muscle mass is regulated by intracellular anabolic and catabolic activities. Increased catabolic activity can shift the balance towards net protein breakdown and muscle atrophy. Mitochondrial oxidative stress activates catabolism and is linked to muscle loss. Reducing mitochondrial oxidative stress is thus a plausible approach to prevent muscle atrophy. We tested this concept in age‐dependent muscle atrophy by genetically overexpressing the mitochondrial antioxidant thioredoxin‐2 (TXN2). Methods We tested the functional role of TXN2 using ageing (n = 7-10 per group) and denervation (n = 3 per group) models in a transgenic mouse line that overexpresses TXN2. We investigated if overexpression of TXN2 blocks muscle loss in these models by examination of muscle weight, fibre size, and fibre number in young (~7 months) and aged (~26 months) TXN2‐transgenic mice and controls. We studied the underlying mechanisms by mRNA and protein assays including transcriptomic profiling, western blot analysis, immunostaining, as well as succinate dehydrogenase, dihydroethidium, and terminal deoxynucleotidyl transferase dUTP nick end labelling staining. Results Overexpression of TXN2 did not significantly alter the baseline skeletal muscle size, weight, fibre type distribution, or expression of mitochondrial respiratory chain components, but it did preserve muscle mass during ageing. The hindlimb muscle mass in aged TXN‐transgenic mice was ~21-24% greater (in tibialis anterior, gastrocnemius/soleus combined, and tibialis anterior/extensor digitorum longus combined) than in age‐matched controls (all P < 0.05). The reduction in both muscle fibre number (872 ± 206 vs, 637 ± 256 fibres in extensor digitorum longus muscle, P < 0.05) and muscle fibre size (1959 ± 296 vs. 1477 ± 564 μm2 in tibialis anterior muscle, P < 0.05) seen in young vs. aged control muscles was not significant in young vs. aged TXN‐transgenic mice (both P > 0.05). Transcriptomic analysis revealed that catabolic genes that are up‐regulated in ageing muscle, including those subserving apoptosis and the ubiquitin‐like conjugation system, were normalized by TXN2 overexpression. Further, overexpressing TXN2 suppressed oxidative stress and caspase‐9/3‐mediated apoptotic signalling in the aged muscle at the protein level. Although denervation and its effects have been considered a component of age‐related muscle atrophy, TXN2 overexpression failed to attenuate atrophy in an acute denervation model (TXN‐transgenic vs. control mice, P > 0.05), despite preventing denervation‐induced oxidative stress and apoptosis. Conclusions Mitochondrial oxidative stress appears to play a crucial role in effecting chronic age‐dependent, but not acute neurogenic, muscle atrophy. Increased TXN2 protects muscle against oxidative stress‐associated catabolic activity in ageing muscle and thus is a potential therapeutic approach to attenuate age‐related muscle atrophy.